2000
DOI: 10.1159/000014437
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes of Plasma Trace Element Concentrations in Chronic Hemodialysis Patients

Abstract: Background: Hemodialysis (HD) patients are at risk of developing trace element imbalances. Methods: The 12 trace elements Cd, Co, Cs, Cu, La, Mg, Mo, Pb, Rb, Sr, Tl and Zn were determined in the plasma (n = 52) of 6 chronic HD patients before and after HD sessions by inductively coupled plasma mass spectrometry. Plasma trace element concentrations were monitored for 6 months. Baseline data have been compared to the concentrations at the end of the observation period to identify a potential reduction or accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 17 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…They found Zn amounts in HD patients lower than those in control groups [3]. Krachler et al [2] found elemental composition changes in plasma and observed a decrease in Mg levels over a 6-month period. In our study, plasma Zn, Cu, and Mg trace element levels of CRF patients, classified according to their HD periods, were compared with a control group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found Zn amounts in HD patients lower than those in control groups [3]. Krachler et al [2] found elemental composition changes in plasma and observed a decrease in Mg levels over a 6-month period. In our study, plasma Zn, Cu, and Mg trace element levels of CRF patients, classified according to their HD periods, were compared with a control group.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with chronic renal failure requiring hemodialysis (HD) are at risk of developing severe trace element imbalances. Medication, the uremic state, the dialysis process, and the quality of water used for dialysis may contribute to such clinical abnormalities in dialyzed uremic patients [2]. Although recent improvement in the dialysis technique prevents some serious complications by changes in trace elements, problems still remained [3].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of these element supplements on CKD patients are also supported by some research studies [19,20]. The majority of the studies that evaluated the status of these TEs focused on CKD patients without dialysis treatment and those receiving hemodialysis (HD), while limited investigations have been conducted regarding CAPD patients [9,21,22,23,24,25,26]. In addition, few studies have been reported on the status of TE excretions in CAPD patients under the special circumstance of this disease, which would provide suggestions for clinical prevention and treatment and would even be available to establish recommendations for supplementation of deficient TEs.…”
Section: Introductionmentioning
confidence: 94%
“…The discussion concerning the role of rubidium as an antidepressant has recently been reopened because a deficiency has been discovered in uremic patients undergoing dialysis treatment [18][19][20][21][22][23][24][25][26][27][28][29][30] . Research is being carried out to discover if this deficiency is due to dialysis or a low rubidium intake in the diet.…”
Section: Rubidium and Uremiamentioning
confidence: 99%